An understanding of lattice strain, defects and disorder in nuclear graphite. (November 2017) - Krishna, Ram; Wade, James; Jones, Abbie N.; Lasithiotakis, Michael; Mummery, Paul M.; Marsden, Barry J.
Abstract: In this study, microstructural parameters, such as lattice dimension, micro-strain and dislocation density, of different neutron-irradiated graphite grades have been evaluated using the diffraction profiles of X-ray diffraction (XRD) and the scattering profiles of Raman spectroscopy. Using Generation-IV candidate graphite samples (grade PCEA, GrafTech), subjected to neutron irradiation at 900 °C to 6.6 and 10.2 dpa, and graphite samples of similar grain size and microstructure taken from the core of the British Experimental Pile Zero reactor, which have been irradiated at 100–120 °C to 1.60 dpa, an investigation is presented on the effect of irradiation dose and temperature on the aforementioned microstructural parameters. Using two complementary techniques in Raman spectroscopy and XRD, which produced agreeable results, the average lateral crystallite size of the two graphites tested was found to decrease with increasing exposure to fast-neutron irradiation or at lower irradiation temperatures. Conversely, dislocation densities and micro-strains were found to increase following the same changes in irradiation conditions. Supporting evidence for the microstructural information obtained is provided by direct observations made using high-resolution transmission electron microscopy. These images demonstrate the presence of irradiation-induced prismatic edge dislocations as well as features that indicate the presence of basal dislocations. They also provide supporting evidence for the progressive deterioration of the graphitic planes via damage mechanisms as proposed in the literature. Graphical abstract: